Semantic methods for functional hybrid modelling - Capper, John (2014)
Equation-based modelling languages have become a vital tool in many areas of science and engineering. Functional Hybrid Modelling (FHM) is an approach to equation-based modelling that allows the behaviour of a physical system to be expressed as a modular hierarchy of undirected equations. FHM supports a variety of advanced language features — such as higher-order models and variable system structure — that sets it apart from the majority of other modelling languages. However, the inception of these new features has not been accompanied by the semantic tools required to effectively use and understand them. Specifically, there is a lack of static safety assurances for dynamic models and the semantics of the aforementioned language features are poorly understood.